The Revolution of Worship - Audy Santoso (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2020)
Christian's view of worship has been revolutionized that bears great consequences in history. To grasp this notion, one needs to understand the concept of time that includes aion (age/ era). There have been many turnovers of Aions in history, but the greatest one was revolutionized by Jesus. What Jesus does was forthtold by David, who revolutionized worship to consists not only of sacrifices but also of praises. The revolution of worship by Jesus bears several implications in our current practice. Worship is not a one dimensional of 'here and now' reality, but in fact a reality that is greater than the church herself.